Efectos del gasto público y la informalidad laboral en el nivel de pobreza crónica en el departamento de Loreto 2012-2022 - Flores Ayarza, Cristian Alan Rey (2024)
The present research is quantitative, causal level and non-experimental in design with longitudinal data. It focused on the study population made up of the quarterly series on public spending, labor informality and the level of chronic poverty calculated by the integrated method in households of the department of Loreto between the years 2012 and 2022. This method defines as chronic poor those individuals who reside in households with at least one unmet basic need and who at the same time are classified as monetary poor. The main objective of the research was to estimate the effects of the independent variables on the level of chronic poverty in Loreto during the aforementioned period. Understanding the factors that contribute to deprivation in the most vulnerable households is crucial to designing effective strategies that promote employment opportunities for low-income families or reduce the inequality gap. According to the econometric model of OLS, it was determined that when public spending increases by 10% the level of chronic poverty is reduced by 0.99%, while when the incidence of labor informality is reduced by 1% the dependent variable is reduced by one 0.52%.